EXTRA-FURNACE STEEL PROCESSING BY RECYCLED SECONDARY ALUMINUM WASTE - I. V. Tribushevskiy; B. M. Nemenenok; G. V. Rumiantseva; M. A. Kulik (Литьë и металлургия, 2018)
The paper presents the results of research on the use of recycled aluminum waste (RAW) during extra-furnace steel processing in ladle refining furnace. It has been established that simultaneously with the deoxidation of refining slags before desulfurization of steel, their liquid mobility increases, which eliminates the need for using fluorspar for these purposes.A thermodynamic analysis of possible reactions of formation of aluminates and calcium aluminosilicates in the refining slag has been carried out. It has been suggested that the cause of thinning of refining slags from the addition of RAW is the formation of a number of low-melting eutectics containing aluminates and calcium aluminosilicates. The composition of briquettes based on RAW for liquefaction of refining slags is proposed. Dependence of the friability and breaking load of briquettes on the content of CaO, the temperature and drying time is established. The data on the composition and properties of the refining slag after treatment with a diluent based on RAW are given.